PENGATURAN POLA ISTIRAHAT DALAM MASA PANDEMI COVID 19 - Angga Indra Kusuma; Billy Emir Rizkanto; Brahmana Rangga; Hayati; Santika Rentika Hadi; Moh Hanafi (Kanigara, 2022)
The government is taking steps to reduce the spread of the covid 19 virus. One of the efforts is to limit social activities through a lock down policy. The closure of schools and gyms as well as the cancellation of sporting events were also carried out, so that learning was carried out online. This will certainly change the physical activity that is usually active to be more passive at home. The purpose of this activity is to educate all school residents about regulating rest patterns as one of the steps to minimize the spread of covid 19. Example of an abstract text. The method used is field observation, drafting needs and licensing plans, implementing activities, and evaluating. The results of this activity were obtained that all school residents had an understanding of covid 19. All school residents were asked to apply adequate and regular rest patterns and pay attention to cleanliness both body and home environment.